A Hands‐On Guide to Brewing and Analyzing Beer in the Laboratory. Issue 1 (13th September 2019) - Thesseling, Florian A.; Bircham, Peter W.; Mertens, Stijn; Voordeckers, Karin; Verstrepen, Kevin J.
Abstract: Beer would not exist without microbes. During fermentation, yeast cells convert cereal‐derived sugars into ethanol and CO2 . Yeast also produces a wide array of aroma compounds that influence beer taste and aroma. The complex interaction between all these aroma compounds results in each beer having its own distinctive palette. This article contains all protocols needed to brew beer in a standard lab environment and focuses on the use of yeast in beer brewing. More specifically, it provides protocols for yeast propagation, brewing calculations and, of course, beer brewing. At the end, we have also included protocols for analyses that can be performed on the resulting brew, with a focus on yeast‐derived aroma compounds. © 2019 The Authors.